Proposal of a gait measurement and evaluation method using an IoRT care-walker - Katsushi Ogawa; Akihiro Yamada; Fumikazu Suwa; Hiroaki Aoyama; Seonghee Jeong (ROBOMECH Journal)
Abstract In Japan, which is an aging society, the number of people with reduced walking ability is expected to increase. Maintaining and improving walking ability is an issue in the rehabilitation field. Therefore, early detection of the risk of fall and other related issues is important in the elderly. By using the IoRT(Internet of Robotic Things) care-walker developed as a gait training device, it is possible to easily and automatically measure the gait characteristics without any special operation. In this paper, we propose an automatic measurement method for gait characteristics using an IoRT care-walker. The proposed method can detect the walking state using motion information obtained from the walker.